Collapse resistance of composite beam-column assemblies with unequal spans under an internal column-removal scenario. (1st March 2020) - Zhong, Wei-hui; Tan, Zheng; Tian, Li-min; Meng, Bao; Song, Xiao-yan; Zheng, Yu-hui
Highlights: The composite beam-column assemblies with unequal span ratios are tested. The contribution coefficients of two-bay beams are proposed in this paper. The composite effect and unequal height-span ratio of two-bay beams are analyzed. Abstract: To investigate the collapse performance of composite beam-column assemblies consisting of three columns and two beams with unequal spans under an internal column removal scenario, static loading tests with either unequal spans (1.4:1 or 0.6:1) or an equal span (1:1) were conducted. Experimental results, including the load-displacement responses, failure modes, internal force development and resistance mechanism, are discussed in detail. Besides, the contributions of different resistance mechanisms to the total resistance of the two-bay beams are quantitatively separated, which include the flexural resistance and catenary resistance of two-bay beams. In addition, finite element models of three specimens are validated based on the test results. Furthermore, the numerical models are used to illustrate the effect of the composite effect and unequal height-span ratio of two-bay beams on the collapse-resistant performance of the assembly. The results showed that the concrete slabs contributed to an increased collapse resistance of the composite beam-column assemblies. Decreasing the beam span resulted in a larger resistance under both mechanisms, whereas increasing the beam height increased the resistance under the flexural mechanism but contributed little to that under the catenary mechanism.